Using machine learning to predict activity chains and mode choice on transportation models - Miranda, Daniele Firme (2020)
Dissertação (mestrado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Civil e Ambiental, 2020.